Does the Transkei population of Haliotis Midae at the eastern edge of its distributional range have a higher thermal tolerance than those in more temperate waters? - Mathebula, Surprise (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The South African perlemoen abalone (Haliotis midae) may be vulnerable to rising temperatures on the East coast of South Africa due to climate change. H. midae is South Africa's most valuable aquaculture species, and it is thus important to understand its physiological ability to adapt to the expected changes and to identify possible management measures to mitigate the impacts of rising temperatures. This project aimed to understand thermal tolerance and growth rates of offspring from two H. midae populations originating from the warm-temperate Central region (Port Elizabeth) and warmer Eastern edge of the species' distribution in the Transkei region. To determine the effects of temperature on the physiological performance of the two abalone populations, growth rates, oxygen consumption rates and critical thermal maxima (CTM) were compared. A laboratory growth trial was conducted at three controlled temperatures, visibly, the 'optimal' temperature for H. midae growth (18 - 20℃), 'pejus' (stressful) temperature (21 - 22℃) and 'critical' temperature (23 - 24℃). Oxygen consumption rates were recorded at optimum (20℃), pejus (22℃) and critical (24℃) temperature using a respirometer. In addition, a farm growth trial with simultaneously spawned cohorts of abalone from the two populations was conducted at ambient temperature (19.5 and 20.0℃). The laboratory growth trial revealed no significant differences in growth rate between the two populations at the three temperature treatments (ANOVA, P > 0.05; df = 2). However, mortalities were high and growth rates low, indicating that the rearing conditions were sub-optimal, possibly masking genetic differences. No significant differences were observed in oxygen consumption rates (ANOVA, P = 0.18; df = 2), and CTM (t-Test, P = 0.31; df = 3) between the two populations. The CTM for both populations was between 29 - 30℃. The farm trial yielded no significant differences in growth rate during the Nursery phase (t-Test, P = 0.25; df = 2), however significant differences in growth rate were observed during the grow out phase with the Central region abalone offspring growing faster than the Eastern edge population (t-Test, P = 0.04; df = 4) indicating the possibility of a genetic difference between the two populations. Further experiments will be required to determine whether the differences observed in the growth trial were genetically or environmentally induced.
Keywords: Haliotis midae -- South Africa -- Indian Coast; Abalones -- South Africa -- Indian Coast; Haliotis midae -- Effect of temperature on -- South Africa -- Indian Coast; Haliotis midae -- Physiology -- South Africa -- Indian Coast; Haliotis midae -- Adaptation -- South Africa -- Indian Coast; Haliotis midae -- Growth -- South Africa -- Indian Coast